Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

CDK19 is disrupted in a female patient with bilateral congenital retinal folds, microcephaly and mild mental retardation - Arijit Mukhopadhyay; Jamie M. Kramer; Gerard Merkx; Dorien Lugtenberg; Dominique F. Smeets; Merel A. W. Oortveld; Ellen A. W. Blokland; Jyoti Agrawal; Annette Schenck; Hans van Bokhoven; Erik Huys; Eric F. Schoenmakers; et al. (Human Genetics, 2010)

Evaluation of the Quick, Easy, Cheap, Effective, Rugged, and Safe (QuEChERS) Approach to Pesticide Residue Analysis - F. J. Schenck; J. E. Hobbs (Bulletin of Environmental Contamination and Toxicology, 2004)

Rapid Solid Phase Extraction Cleanup for Pesticide Residues in Fresh Fruits and Vegetables - F. J. Schenck; V. Howard-King (Bulletin of Environmental Contamination and Toxicology, 1999)